Draft Five Year Plan 1978-83 General Areas Vol. III Government of Assam - Planning Commission (Planning Commission, 1978)
One strategy adopted is to propose the modernisation and augmentation of the completed Medium Projects so that their utility is increased in an economic manner and the Command Area Development is done for fuller utilisation of the created potential. Under the programme, the Jamuna, Shukla and the Long Schemes are proposed to be modernised and improved.
Government of Assam, Planning and Development Department